Children's Innocence Discourse: Are They Vulnerable? - Hanifah, Siti (Kiddie: Early Childhood Education and Care Journal, 2024)
Early childhood is often perceived as a time of innocence in their perception of the world; however, questions arise about whether this innocence truly makes them vulnerable to risky situations. This research aims to provide a deeper understanding of the factors influencing children's innocence and its connection to their vulnerability to risky situations. The research method employed is a Systematic Literature Review. Data analysis techniques involve thematic data analysis. Article collection was conducted for three months from October to December 2023, utilizing secondary data. The secondary data sources consist of high-quality journal articles nationally and proceedings with a predefined focus. These articles were obtained from the Google Scholar database using keywords such as "innocence discourse," "Michael Foucault," "truth regimes," and "early childhood education." These findings offer crucial insights for parents, educators, and practitioners in carefully handling child development, emphasizing environmental factors influencing children's perceptions of risky situations. In the context of the discourse on children's innocence, the importance of protecting and ensuring the welfare of children as human individuals demands serious attention. A holistic perspective is required to comprehend the complexity of children, emphasizing a comprehensive focus on their rights, needs, and welfare as they grow and develop. Anak usia dini sering dianggap polos dalam persepsianya terhadap dunia, namun, pertanyaan muncul mengenai apakah kepolosan ini benar-benar membuat mereka rentan terhadap situasi berisiko. Penelitian ini bertujuan untuk memberikan pemahaman yang lebih mendalam mengenai faktor-faktor yang mempengaruhi kepolosan anak dan bagaimana kepolosan ini berkaitan dengan tingkat rentan mereka terhadap situasi berisiko. Metode penelitian adalah Systematic Literature Review. Teknik analisis data menggunakan data tematik. Pengumpulan artikel dilakukan selama tiga bulan pada bulan Oktober sampai Desember 2023 dengan menggunakan data sekunder. Sumber data sekunder yang digunakan terdiri dari artikel jurnal yang bermutu baik secara nasional dan prosiding dengan fokus yang telah ditentukan sebelumnya. Artikel-artikel ini diperoleh dari database Google Scholar dengan menggunakan kata kunci seperti "wacana kepolosan," "michael foucault," "rezim kebenaran," dan "pendidikan anak usia dini." Hasil ini memberikan wawasan penting bagi para orang tua, pendidik, dan praktisi dalam menangani perkembangan anak dengan lebih cermat, memberikan perhatian pada faktor-faktor lingkungan yang memengaruhi persepsi anak terhadap situasi berisiko. Dalam konteks wacana kepolosan anak, pentingnya perlindungan dan kesejahteraan anak sebagai individu manusia menuntut perhatian yang serius. Diperlukan sudut pandang yang holistik untuk memahami kompleksitas anak, termasuk pemberian perhatian yang utuh terhadap hak-hak, kebutuhan, serta kesejahteraan anak saat mereka tumbuh dan berkembang.